BUS SEKOLAH: TINJAUAN LAYANAN DAN KESELAMATAN - Tangkudung, Ellen S.W. (FSTPT Indonesia, 2015)
School transportation may be one alternative that can be applied to change the travel behavior of students who are not efficient is the use of vehicles with an occupancy level and a low level of safety as a personal four-wheeled vehicles and motorcycles, as well as improving public transportation services for students who do not have private vehicles. Free school bus services in Jakarta not reach all areas, but with the addition of the fleet doubled in the year 2013 and determination in accordance with the needs of the students, the number of students who use the school bus more and more at an average of 11,000 students per day. Guarantees timeliness arrived at school, access to adequate shelter, comfort, safety and security for the school bus in the results of the study into the effectiveness of the provision of the parameters of the school bus by the Jakarta administration. But still have improved the safety factor for the low parameter concerns the other riders on the existence of the school bus when raising and lowering the passenger at the stop.